Tracking the degradation pathway of three model aqueous pollutants in a heterogeneous Fenton process. Issue 2 (April 2019) - Cohen, Mélanie; Ferroudj, Nassira; Combes, Audrey; Pichon, Valérie; Abramson, Sébastien
Graphical abstract: Highlights: The degradation pathway of three water pollutants by Fenton process was investigated. γ-Fe2 O3 /SiO2 microspheres were used as magnetically separable heterogeneous catalyst. Different analytical methods were used. New transformation products were identified for each pollutant. It was possible to propose an overall transformation pathway for each pollutant. Abstract: The degradation pathway of three model aqueous pollutants, methyl orange, methylene blue, and paranitrophenol, in a Fenton process based on the use of maghemite/silica microspheres as magnetically separable heterogeneous catalyst was investigated. The utilization of different analytical methods, including UV–vis spectroscopy, non-purgeable organic carbon (NPOC) measurements, quadrupole-time-of-flight high resolution mass spectrometry (Qtof-HRMS), liquid chromatography coupled with mass spectrometry (LC–MS), and ion chromatography (IC) allowed the identification at different times of many transformation products for each pollutant. These analyses confirmed first the existence of intermediates which have been already evidenced in previous studies on the advanced oxidation of these pollutants. However, new products were also identified, particularly thanks to the highly accurate Qtof-HRMS analyses. The evolution with time of the main intermediate compounds was monitored by LC–MS. It was then possible to propose an overall transformation pathway for each pollutant. The same classes of reactions, especially ring-hydroxylations and N-demethylations, were observed for the three pollutants, although specific features were also pointed out. While some common features with other advanced oxidations processes were found, the highlighted specificities could be related to the selection of the catalyst and to the experimental conditions used for the degradation tests.